Transformation of Economic Growth Momentum and Policy Choice: A Case Study of Guangdong Province in China - Feng Luo; Feng Chen; Dandan Yang; Simin Yang (Discrete Dynamics in Nature and Society)
The mystery of China’s economic growth has been widely concerned by the world. However, little attention has been paid to the transformation of the economic growth momentum of Guangdong Province, which has long occupied the top in China’s economic growth. This paper analyzes the evolution and the transformation of the momentum source of economic growth in Guangdong Province from 1979 to 2019, using Total Factor Productivity Growth Decomposition method. The results show that capital investment contributes the most to economic growth, the contributions of total factor productivity, and labor input rank second and third, respectively; the change of the contribution of each momentum source to GDP growth mainly comes from the impact of the secondary industry. Both industrial capital productivity and capital allocation structure play a negative role in driving the overall capital productivity, and both industrial labor productivity and labor allocation structure play a positive role in driving the overall labor productivity. Industrial factor productivity and industrial factor allocation structure play a major positive role and a weak negative role in promoting economic growth, respectively. Our findings provide some ideas on how to maintain economic growth in the new era especially for the developing countries.